PERAN DATA GONVERNANCE DALAM MENINGKATKAN KUALITAS DATA UNTUK PENGAMBILAN KEPUTUSAN BISNIS YANG LEBIH BAIK - Eliza Putri; Muhamammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In today's digital era, data has become a strategic asset for companies. However, the benefits of data can only be obtained if the data is of high quality. Data Governance is present as a framework that allows organizations to manage data systematically to ensure data accuracy, consistency, and consistency. This article discusses the importance of Data Governance in improving data quality and how its implementation contributes to better business decision making. The method used is a literature study from various academic sources and industry practices from 2018 to the present. Data is a strategic asset that underlies business decision making. However, low data quality is often an obstacle to producing accurate and effective decisions. This essay discusses the role of data governance in improving data quality and how it impacts the business decision-making process. By referring to several studies, including a study conducted in 2020, this essay confirms that strong data governance can improve data accuracy, consistency, and consistency, thereby supporting sharper and more adaptive business strategies.